Co-infection of SARS-CoV-2 with other respiratory pathogens in patients with liver disease. Issue 10 (3rd October 2022) - Samal, Jasmine; Agarwal, Reshu; Soni, Anushka; Pandey, Amit; Thapar, Shalini; Gupta, Ekta
Abstract : Respiratory illness caused by SARS-CoV-2 (severe acute respiratory syndrome coronavirus 2) was first documented in Wuhan, China, in December 2019, followed by its rapid spread across the globe. Accumulating evidence has demonstrated viral/bacterial co-infection in the respiratory tract could modulate disease severity and its outcome in COVID-19 infection. In this retrospective study, 300 chronic liver disease patients with radiologically confirmed lower respiratory tract infection were enrolled from September 2020 to December 2021. In all of them, along with SARS-CoV-2, other respiratory viral/bacterial pathogens were studied. In total, 23.7 % ( n =71) patients were positive for SARS-CoV-2. Among the positive patients, 23.9 % ( n =17) had co-infection with other respiratory pathogens, bacterial co-infections being dominant. The SARS-CoV-2 negative cohort had 39.7  % positivity ( n =91) for other respiratory pathogens, the most common being those of the rhinovirus/enterovirus family. Ground glass opacity (GGO) with consolidation was found to be the most common radiological finding among SARS-CoV-2 positive co-infected patients, as compared to only GGO among SARS-CoV-2 mono-infected patients. Accurate diagnosis of co-infections, especially during pandemics including COVID-19, can ameliorate the treatment and management of suspected cases.